EVENT-MARKETING – FEATURES OF APPLICATION IN MODERN TOURISM - Vlasenko , O. B. (The actual problems of regional economy development, 2016)
In the article analyzed the modern features of the development and using of event-marketing. Showed the conditions of the essence and characteristics of event management, its principles and methods of application. Characterized the features and importance of tourism and the benefits of application of event marketing as a promising method of indirect marketing communications. Used examples of practical application of event marketing activity. Determined correlation of event management and marketing and its subordination to the event marketing purposes. JEL: M 31